REDUPLICATION IN SUNDANESE LANGUAGE - Iin Nurhayati; Sutiono Mahdi (Universitas Islam Sumatera Utara (UISU), 2018)
Linguistically speaking, Sundanese has a wide range of reduplicated words and as well delivers different meaning in a different words form wherever it be added by suffixes, infixes, or prefixes. This research try to presents and classify kinds of reduplication in Sundanese, in which stage they belong and how they can be different or not semantically and morphologically, and how they can presumably be similiar or different from one another. The data collection will involve correspondence to be asked about some word that can be reduplicated, using semantics and morphology as the approach to see the occurrence. Based on the data that has been investigated and classified, Sundanese reduplication can be applicable to all semantics properties. Thus, if Augmentation can be expressed by Sudanese reduplication, so does Diminution. On the other hand, if intensification can also be expressed by means of reduplication in Sudanese, so attenuation can also be expressed by Sudanese reduplication. Also if Sudanese root word is bound by affixation whether it be in prefix, infix, or suffix, its lexical and grammatical meaning can changed.